FGF21 as a Stress Hormone: The Roles of FGF21 in Stress Adaptation and the Treatment of Metabolic Diseases - Kim, Kook Hwan; Lee, Myung-Shik (Diabetes & metabolism journal, 2014)
Fibroblast growth factor 21 (FGF21) is an endocrine hormone that is primarily expressed in the liver and exerts beneficial effects on obesity and related metabolic diseases. In addition to its remarkable pharmacologic actions, the physiological roles of FGF21 include the maintenance of energy homeostasis in the body in conditions of metabolic or environmental stress. The expression of FGF21 is induced in multiple organs in response to diverse physiological or pathological stressors, such as starvation, nutrient excess, autophagy deficiency, mitochondrial stress, exercise, and cold exposure. Thus, the FGF21 induction caused by stress plays an important role in adaptive response to these stimuli. Here, we highlight our current understanding of the functional importance of the induction of FGF21 by diverse stressors as a feedback mechanism that prevents excessive stress.